Borrelia-Induced Koebner Phenomenon in Psoriasis: A Role of Local TNF-α Production? - Schulmeyer, Lena; Fleißner, Janik; Überschaar, Simon; Goebeler, Matthias; Kerstan, Andreas (Archives of Clinical and Medical Case Reports, 2025)
Psoriasis vulgaris is a chronic, immune-mediated inflammatory skin condition. Moderate to severe forms of the disease are effectively treated with biologics targeting Interleukin-(IL-)17 and tumor necrosis factor alpha (TNF-α), which are both produced by T cells, as well as dendritic cell-derived IL-23. In addition to genetic predispositions, environmental factors affect the onset and severity of symptoms [1]. The Koebner phenomenon (KP) describes the emergence of skin lesions at sites of nonspecific trauma, like scratching, tattooing, or exposure to chemical irritants, on clinically unconspicous skin [2,3]. This report discusses a Borrelia-induced KP in a psoriasis patient on ustekinumab therapy.